(untitled) (International Journal of Biomedical and Advance Research, 2016)
Introduction: The factual knowledge says that interactivity leads to better learning outcomes. MCI has recommended interactive and innovative teaching but it is rare to find studies that have emphasized on faculty development and so this research work is a step-stone in medical education. Aim and objectives: To compare the educational effectiveness of interactive lectures with didactic lectures as well as to acknowledge the preferred mode of teaching in a large group through the perception of students and faculties. Methods: Randomized controlled Trial with cross-over was conducted among the 7th semester students (112) in RMCH, Bareilly for a period of 3 months. Each group (56) were taught interactive (by Think-Pair-Share, buzz groups, peer instructions, questioning) and didactic lectures respectively with cross-over. Pre and Post tests were conducted in each session using MCQs. Feedback from the students (112) and faculty (11) were filled subsequently using Likerts scale. The data was analyzed by using the SPSS and P values 0.05 considered significant. Results: Statistically significant difference (p 0.01) was found in pre-test and post-test scores of both groups. Also, the gain through the two was also found to be statistically significant (p-value 0.001). Interactive teaching in medical education was agreed upon by the students and faculties as a more active and better way of learning for attaining the specific learning objectives. Conclusion: Learning was enhanced through interactive lectures as compared to didactic ones and there was positive perception among students and faculties, so it is strongly recommended to train the faculty members in the various interactive methods but still further research is needed on a larger sample to improve external validity.